Law Enforcement Against Action Criminal Sexual Violence in Gender Based Digital Space in Indonesia - Ivan Zairani Lisi; Khristyawan Wisnu Wardana; Deny Slamet Pribadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Sexual violence in the digital space can occur in various motives, such as Flaming, which is an act of harassment committed personally on social media, where the perpetrator insults, attacks, or humiliates the victim through abusive words, private photos, or messages that lead to sexual activity. In the context of digital sexual violence. This form of harassment aims to cause the victim distress, fear, or embarrassment, and can cause psychological trauma. To protect victims, the law needs to impose sanctions against sexual harassment committed through electronic media. In the Indonesian legal system, several laws have been implemented to follow up and address this kind of crime, including the Electronic Information and Transaction Law (ITE Law), the Criminal Code (KUHP), and the Sexual Violence Crime Law (TPKS Law), so that perpetrators of sexual violence in digital spaces are expected to be subject to strict criminal sanctions. Laws are an important step in law enforcement and victim protection. However, effective implementation and public education are needed to achieve these goals. Therefore, there is a need for training for law enforcement officials to better understand and be able to handle appropriate cases of digital sexual violence and community counselling and public education to increase public awareness of electronic sexual violence.